Vertical distribution of benthic invertebrate larvae during an upwelling event along a transect off the tropical Brazilian continental margin - Yoshinaga, Marcos Y.; Sumida, Paulo Y. G.; Silveira, Ilson C. A.; Ciotti, Aurea M. [UNESP]; Gaeta, Salvador A.; Pacheco, Luiz F. C. M.; Koettker, Andrea G. (Elsevier B.V., 2010)
Abundance and composition of marine benthic communities have been relatively well studied in the SE Brazilian coast, but little is known on patterns controlling the distribution of their planktonic larval stages. A survey of larval abundance in the continental margin, using a Multi-Plankton Sampler, was conducted in a cross-shelf transect off Cabo Frio (23 degrees S and 42 degrees W) during a costal upwelling event. Hydrographic conditions were monitored through discrete CDT casts. Chlorophyll-a in the top 100 m of the water column was determined and changes in surface chlorophyll-a was estimated using SeaWiFS images. Based on the larval abundances and the meso-scale hydrodynamics scenario, our results suggest two different processes affecting larval distributions. High larval densities were found nearshore due to the upwelling event associated with high chlorophyll a and strong along shore current. on the continental slope, high larval abundance was associated with a clockwise rotating meander, which may have entrapped larvae from a region located further north (Cabo de Sao Tome, 22 degrees S and 41 degrees W). In mid-shelf areas, our data suggests that vertical migration may likely occur as a response to avoid offshore transport by upwelling plumes and/or cyclonic meanders. The hydrodynamic scenario observed in the study area has two distinct yet extremely important consequences: larval retention on food-rich upwelling areas and the broadening of the tropical domain to southernmost subtropical areas. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SE Brazilian coast (23 degrees S and 42 degrees W); Shelf dynamics; Coastal upwelling; Zooplankton; Invertebrate larvae